Whispers and lies - Fielding, Joy (New York : Pocket Books, 2003)
A single, middle-aged woman's peaceful Florida beachfront life is shattered by the arrival of a mysterious younger woman in her neighborhood.
National College of Business and Arts
Keywords: Single women -- Fiction; Suspense fiction